EFEKTIVITAS SENAM KAKI DIABETIK TERHADAP PENURUNAN KADAR GULA DARAH PADA PASIEN DIABETUS MELLITIUS DI DESA MULUR - Nita Yunianti Ratnasari; Wahyu Susilowati (Akademi Keperawatan Giri Satria Husada Wonogiri, 2018)
Diabetes Mellitus is a chronic metabolic disease wherein diabetics cannot produce enough insulin or the body is unable to use insulin effectively so that excess sugar in the blood. To regulate blood sugar levels can be done pharmacologically or taking drugs or with insulin injections, to regulate blood sugar levels can be done by non-pharmacological means by means of diabeticfoot exercise. This type of research is qualitative with a descriptive case study approach. The population in this study were all residents of Rt / Rw 02/01 in Mulur sub-village, Bendosari sub-district, sukoharjo regency who had Diabetus Mellitus. Sample respondents were 3 respondents. The instrument uses standard operating procedures (SOP), measurement of blood sugar (GDS) and observation sheets. Observations made from all respondents showed that after doing diabetic foot exercises for 3 times a week, the results of blood sugar levels in respondent I = 160 mg / dl, respondent II = 155mg / dl and respondent III = 148mg / dl. The results of the analysis conducted from all respondents obtained data that before and after doing diabetic foot exercises there is a change in each respondent which decreases gradually, thus the problem is partially resolved and interventions arecontinued.